Poziom uzależnienia od nikotyny oraz motywacja do zaprzestania palenia tytoniu w wybranej grupie Polaków = Level of nicotine addiction and motication for qutting smoking in chosen group of Poles - Katarzyna Sawicka; Robert Łuczyk; Katarzyna Zięba; Marta Łuczyk (Kazimierz Wielki University, 2015)
Sawicka Katarzyna, Łuczyk Robert, Zięba Katarzyna, Łuczyk Marta. Poziom uzależnienia od nikotyny oraz motywacja do zaprzestania palenia tytoniu w wybranej grupie Polaków = Level of nicotine addiction and motivation for quitting smoking in chosen group of Poles. Journal of Education, Health and Sport. 2015;5(8):395-416. ISSN 2391-8306. DOI10.5281/zenodo.29693 http://dx.doi.org/10.5281/zenodo.29693 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A395-416 https://pbn.nauka.gov.pl/works/614567 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.07.2015. Revised 24.08.2015. Accepted: 24.08.2015.   Poziom uzależnienia od nikotyny oraz motywacja do zaprzestania palenia tytoniu w wybranej grupie Polaków Level of nicotine addiction and motivation for quitting smoking in chosen group of Poles   Katarzyna Sawicka1, Robert Łuczyk1, Katarzyna Zięba2, Marta Łuczyk3   1Katedra Interny z Zakładem Pielęgniarstwa Internistycznego, Wydział Nauk o Zdrowiu  Uniwersytetu Medycznego w Lublinie 2Absolwentka Wydziału Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 3Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie   Adres do korespondencji: katesawicka@wp.pl   Streszczenie Wstęp: Palenie tytoniu jest poważnym problemem zdrowotnym, społecznym i ekonomicznym w Polsce i na całym świecie [16]. Podejmowane przez Światową Organizację Zdrowia (WHO) liczne działania antynikotynowe nie przynoszą oczekiwanych rezultatów. Palenie tytoniu jest nadal powszechne powodując poważne konsekwencje dla zdrowia publicznego [1]. Materiał i metoda: Badanie zostało przeprowadzone od lipca do sierpnia 2014 roku. Grupę badaną stanowiły osoby palące papierosy od 25 - 70 roku życia. Respondenci wyrażający chęć wzięcia udziału w badaniu otrzymali zestaw testów składający się z autorskiej metryczki oraz wystandaryzowanego narzędzia: Testu uzależnienia od nikotyny wg Fagerströma oraz Testu motywacji do zaprzestania palenia wg dr Niny Schneider. Test uzależnienia od tytoniu wg Fagerströma mierzy głębokość uzależnienia biologicznego od nikotyny. Kwestionariusz składa się z 7 pytań, za każdą z odpowiedzi można otrzymać od 0 do 3 punktów. Maksymalna liczba punktów wynosi 12. Test motywacji do zaprzestania palenia tytoniu wg Niny Schneider służy do pomiaru gotowości do zaprzestania palenia. Składa się on z 12 pytań, na które respondent odpowiada "tak" lub "nie". Przewaga odpowiedzi "tak" świadczyć ma o motywacji do leczenia, przewaga odpowiedzi "nie" świadczy o braku chęci leczenia. Wyniki badań i wnioski: Na podstawie przeprowadzonych badań i analizy ich wyników wyciągnięto następujące wnioski: - osoby palące nie są w większości uzależnione od nikotyny, - motywację do zaprzestania palenia mają częściej osoby nieuzależnione od nikotyny, - uzależnieni od nikotyny są częściej mężczyźni, osoby starsze, pracownicy fizyczni, w mniejszym stopniu od nikotyny uzależnione są osoby z wykształceniem wyższym, - bardziej zmotywowane do rzucenia palenia są kobiety, - wiek, wykształcenie i status zawodowy nie wpływają na motywację do zaprzestania palenia, - osoby, u których zdiagnozowano chorobę częściej były uzależnione od nikotyny niż osoby zdrowe, - występowanie choroby wśród badanych nie wpływa na motywację do zaprzestania palenia, - osoby, które palą dłużej są częściej uzależnione od nikotyny niż osoby palące krócej, - okres palenia papierosów nie wpływa na motywację do rzucenia nałogu, - czynnik zdrowotny ma największy wpływ na zerwanie z nałogiem palenia tytoniu przez palaczy.   Słowa kluczowe: palenie tytoniu, uzależnienie, motywacja do rzucenia palenia.   Abstract Introduction: Smoking is a serious social and economic health problem in Poland and worldwide [16]. Numerous anti-smoking actions taken by the World Health Organization (WHO) do not bring expected results. Smoking is still universal thing, causing serious consequences for the public health [1]. Materials and methods: The study was conducted from July up to August 2014. Individuals smoking cigarettes constituted the examined group from 25 - 70 of year of age. Respondents expressing desire for the participation in the study received the set consisting of the author's certificate and the standardized tool: the nicotine addiction test according to Fagerström and of motivation test for ceasing smoking according to Dr. Nina Schneider. Smoking tobacco test according to Fagerström measures the intensity of biological dependence on nicotine. The questionnaire consists of 7 questions, for every of reply, it was possible to receive from 0 to 3 points. The maximum number of points reaches 12. The test of motivation for ceasing smoking according to Nina Schneider is used for the measurement of the readiness to quit the habit. It consists of 12 questions which the respondent answers as: "yes" or "not". Majority of the reply "yes" proves the motivation for the treatment, majority of the reply "not" attests to the indisposition of the treatment. Results and conclusions: Based on conducted study and analysis of the results, the following conclusions were drawn: - smoking individuals aren't largely dependent on nicotine, - the persons nondependent on nicotine more often have motivation for ceasing smoking - men, elderly people, manual workers are more often dependent on nicotine, individuals with higher education are dependent on nicotine to a lesser degree, - more motivated for giving up smoking are women, - the age, the education and the professional status don't influence to motivation for ceasing smoking, - individuals at whom illness was diagnosed have been more often depended on nicotine than healthy persons, - prevalence of disease amongst the examined doesn't influence to motivation for ceasing smoking, - who have smoked longer are more often dependent on nicotine than persons smoking more briefly, - the period of the cigarette smoking doesn't influence to motivation for quitting the habit - the health determinant has most considerable influence as for quitting tobacco addiction by smokers.   Keywords: smoking tobacco, addiction, motivation for quitting smoking.